Play, Conversation or Maybe Picture: The Teachers` Research of the World of a Child - Kamila Zdanowicz-Kucharczyk (University of Lower Silesia, 2015)
I do research on the world of a child from a few years, trying to find the most suitable way to reach a child. The longer I do research, however, the more and more doubts: do I really come close to the child`s world? Maybe it is only an adult`s construct of a child`s reality. In this article I present my and students` experiences with research on children, which we did during the research project Innovative methods in early childhood education. I try to answer questions: who should research a child`s world? Where, and how? I respond to doubts: how to distinguish child's perspective from an adult's\; how to avoid the power relation in research. Using my experiences, I resolve the problem by present the Alison Clark mosaic approach in research with children.